Misplaced IUCD: a case report - Raj, Aman Deep; Singh, M. K.; Soma, Murali Mohan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Contraception is a national emergency, essential in a developing country like India. Intrauterine contraceptive devices (IUCDs) are amongst the most frequently used methods of contraception. The patients with misplaced IUCDs may present with pregnancies or ‘lost strings’ or they may remain asymptomatic and/ or may have recurrent pregnancy losses and may become pregnant as in our case.